2011
DOI: 10.1007/s10103-011-0971-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines are suppressed by light-emitting diode irradiation of P. gingivalis LPS-treated human gingival fibroblasts

Abstract: Human gingival fibroblasts (hGFs) play an important role in the inflammatory reaction to lipopolysaccharide (LPS) from P. gingivalis, which infects periodontal connective tissue. In addition, although light-emitting diode (LED) irradiation has been reported to have biostimulatory effects, including anti-inflammatory activity, the pathological mechanisms of these effects are unclear. This study examined the effects of 635-nm irradiation of P. gingivalis LPS-treated human gingival fibroblasts on inflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 29 publications
1
32
0
2
Order By: Relevance
“…In the indirect irradiation group, phosphorylation of C-Raf and Erk1/2 increased. In another study [49] the same group used a similar system (direct PBM on HGF + LPS) and showed that 635 nm PBM reduced IL6, IL8, p38 phosphorylation, and increased JNK phosphorylation. They explained the activation of JNK by the growth promoting effects of PBM.…”
Section: Effects Of Pbm On Nf-kbmentioning
confidence: 99%
“…In the indirect irradiation group, phosphorylation of C-Raf and Erk1/2 increased. In another study [49] the same group used a similar system (direct PBM on HGF + LPS) and showed that 635 nm PBM reduced IL6, IL8, p38 phosphorylation, and increased JNK phosphorylation. They explained the activation of JNK by the growth promoting effects of PBM.…”
Section: Effects Of Pbm On Nf-kbmentioning
confidence: 99%
“…It has been shown in vitro that inflammation elicited by Porphyromonas gingivalis LPS ( Pg ‐LPS) can be suppressed by irradiating human gingival fibroblasts with visible red (635–670 nm) light (10). In this study, we devised a technique to directly irradiate the diseased gingival tissue with 660 nm LED light at a range of energy densities after debridement and detoxification in vivo .…”
mentioning
confidence: 99%
“…a) efeito do grupo; b) efeito do tempo; c) interação grupo tempo. marcadamente das citocinas próinfl amatórias 21 , as quais levam a diminuição na atividade autonômica, sobretudo vagal [24][25] . No entanto, não observamos efeitos da LED fototerapia no presente estudo comparada com a situação placebo.…”
Section: Discussionunclassified
“…Seu mecanismo de ação se dá mediante aumento da atividade metabólica intracelular 19 aliada a uma diminuição da produção de agentes pró-infl amatórios [19][20][21][22][23] e marcadores de dano muscular 23 , e a diminuição desses, por sua vez, pode acarretar efeitos sistêmicos traduzidos em aumento na atividade parassimpática [24][25] e diminuição do estresse percebido [26][27] . Embora inconclusivos, principalmente pela escolha dos metabólitos (ex: creatina quinase e lactato sanguíneo), modelo de exercício e aplicação de delineamento tranversais, estudos apontam para um efeito positivo da fototerapia.…”
Section: Sujeitosunclassified